Overweight and obesity in children aged 3–13 years in urban Cameroon: a cross-sectional study of prevalence and association with socio-economic status. Issue 1 (December 2017) - Choukem, Simeon-Pierre; Kamdeu-Chedeu, Josiane; Leary, Sam; Mboue-Djieka, Yannick; Nebongo, Daniel; Akazong, Christoph; Mapoure, Yacouba; Hamilton-Shield, Julian; Gautier, Jean-François; Mbanya, Jean
Abstract Background Childhood overweight/obesity is increasing rapidly in developing countries. There is a need to provide more evidence on its burden in sub-Saharan Africa, and to identify associated factors in order to set preventive measures. We aimed to determine the prevalence of overweight/obesity and assess its association with the socioeconomic status in nursery and primary school children in urban Cameroon. Methods In this cross-sectional study, we included by multi-staged cluster random sampling 1343 children from high (HSES, n  = 673) and low (LSES, n  = 670) socioeconomic status schools in Douala. Parent/child demographic data were collected, and children's anthropometric parameters were measured using validated methods. The World Health Organization body mass index-for-age reference curves were used. Results The prevalence of overweight/obesity was 12.5% (13.2% in girls, 11.8% in boys). The risk of overweight/obesity was 2.40 (95% CI 1.70, 3.40) higher in HSES children compared to LSES after adjusting for age and gender. However this association was attenuated to 1.18 (95% CI 0.59, 2.35) once adjustment had been made for a range of potential confounders. Conclusions Overweight/obesity is relatively common in sub-Saharan African children and prevalence is associated with HSES. However, this association may be mediated by sweet drink consumption, passive means of travel to school and not doing sport at school. We suggest that these potentially modifiable behaviors may be effective targets for obesity prevention. Further studies should specifically focus on unhealthy behaviors that mediate overweight/obesity as well as other non communicable diseases in children.